EVALUATION OF PEANUT GENOTYPES RESISTANCE TO LEAF SPOT (Cercospora personatum) AND RUST DISEASE (Puccinia arachidis) - -, Sumartini (Proceeding of International Congress, 2014)
The study was conducted in the greenhouse of Malang Research Institute for Legumes and Tuber Crops,July â October 2013. Twenty peanut genotypes were tested, each genotype were planted in five plastic pots(Î¦ = 30cm), 2 peanut seeds/pot. Inoculation of rust spore suspension (density of 20,000 spores / ml ) at 3weeks after planting by spraying it to the leaves of peanut. Rust disease observation was done by given avalue to the leaves that covered leaf spot or rust disease and refers to Subramamyam (1995 ). Out of 17 peanutgenotypes tested, one genotype was resistant (R) , 8 genotypes were moderately resistant (MR), 8genotypes were moderately susceptible (MS) against leaf spot disease. Moreover three genotypes wereresistant (R), three genotypes were moderately resistant (MR) , 10 genotypes were moderately susceptible(MS) , and one genotype was susceptible (S) against rust diseases.Keywords: peanut, leaf spot and rust disease, resistance.